Attracting Capital to Africa - Wolfensohn, James D. (World Bank, Washington, DC, 2017)
James D. Wolfensohn, President of the World Bank Group, stated unequivocal financial commitment to and belief in Africa’s future. Africa is not without its problems. He noted that 200 million people live in poverty, earning under a dollar a day. The Bank is investing at the rate of nearly $3 billion a year on top of the $17 billion already put into the region. There has been a real change in the investment climate not only for international investors but also for domestic investors. It is in partnership with the private sector that Africa finds a profound opportunity to change the continent. We can help through the International Finance Corporation (IFC) and Multilateral Investment Guarantee Agency (MIGA) to provide assistance with financing and insurance against risk. The Bank is very keen to play part in assisting the flow of private sector funding. We see that Africa wants to succeed and is being led by people who want to lead their countries to success. Their optimism will be fulfilled only if there is a real partnership.